2004
DOI: 10.1103/physrevb.70.184501
|View full text |Cite
|
Sign up to set email alerts
|

Mott insulators, no double occupancy, and non-Abelian superconductivity

Abstract: SU (4) dynamical symmetry is shown to imply a no-double-occupancy constraint on the minimal symmetry description of antiferromagnetism and d-wave superconductivity. This implies a maximum doping fraction of 1 4 for cuprates and provides a microscopic critique of the projected SO(5) model. We propose that SU (4) superconductors are representative of a class of compounds that we term non-abelian superconductors. We further suggest that non-abelian superconductors may exist having SU (4) symmetry and therefore cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 13 publications
(75 citation statements)
references
References 7 publications
1
74
0
Order By: Relevance
“…[1]. We further propose that the similarity of cuprate and Fe-based phenomenology indicates that non-abelian superconductivity for the FeAs superconductors is based on the same SU(4) symmetry that explains the phenomenology of the cuprates, thus providing a unified picture of Cu and Fe based superconductors.…”
Section: A Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1]. We further propose that the similarity of cuprate and Fe-based phenomenology indicates that non-abelian superconductivity for the FeAs superconductors is based on the same SU(4) symmetry that explains the phenomenology of the cuprates, thus providing a unified picture of Cu and Fe based superconductors.…”
Section: A Introductionmentioning
confidence: 99%
“…In Ref. [1] we demonstrated that non double occupancy for pairs in the real space is a sufficient condition to guarantee that the minimal closed algebra is SU(4), independent of detailed microscopic considerations such as the orbital or spin symmetry of the gap and the associated structure of the pairs.…”
Section: B Cuprate and Fe-based Phenomenologymentioning
confidence: 99%
See 3 more Smart Citations